Determination of Caseinomacropeptide in Brazilian Bovine Milk by High-performance Liquid Chromatography–Mass Spectrometry. (2nd September 2017) - Lenardon, Layane; Meneghini, Leonardo Zanchetti; Hoff, Rodrigo Barcellos; Motta, Tanara Magalhães Campos; Pizzolato, Tânia Mara; Ferrão, Marco Flôres; Bergold, Ana Maria
ABSTRACT: Milk adulteration is a concern in many countries, including Brazil. There are many compounds used as adulterants, including cheese whey, a by-product of cheese. Recently, we have developed a proteomic-like technique for separation and characterization of caseinomacropeptide using liquid chromatography coupled to mass spectrometry with electrospray ionization. Caseinomacropeptide is important because it can be used as marker when cheese whey adulteration is performed in bovine milk. Furthermore, it is difficult to establish reference values for caseinomacropeptide levels because of the variation of milk composition. The aim of this study was to verify the average value for caseinomacropeptide present in bovine raw milk collected by Federal Inspection Service from five regions of Brazil (north, northwest, west central, south, southeast). Survey sampling was divided into two stages: first one, a data set 1 (regional sampling) was collected only from the south during a year. This data sampling was used to estimate the data set 2 (national sampling). A largest extreme value was suggested as a model for caseinomacropeptide distributions for national sampling. The data set showed 2.52 mg L −1 as the mean and 4.80 mg L −1 for the standard deviation based on a sampling size of 170 units collected across Brazil. The findings are useful to understand the presence of caseinomacropeptide, especially when no adulteration or the absence of good practices is present.